Evaluation of Job Performance Among Administrative Staff of First Division and Premier League Handball Clubs in Southern Region - Abdullah Abdulmohsen Khalaf; Saadoun Qasim Lazim (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
Importance of this research lies in need to inform those involved in and interested in handball that there must be a scale that provides an objective numerical value for evaluating functional performance of club administrations supervised by sub-federation or central federation. This numerical assessment serves as evidence of progress achieved in organizational performance, and thus this metric evaluates efforts of administrators or demonstrates extent of their work.  research problem arises from importance of diagnosing current state of performance.  job performance of employees in sports clubs is one of most important organizational variables for success of work in government departments, organizations, and institutions, as it will reflect on administrative performance of employees due to its significant impact on achieving goals.  efficient and effective planning demonstrates importance of understanding nature and essence of prevailing job performance in its various dimensions within any public or private organization. Therefore, researcher defined her research problem with following question: What is level of job performance of administrators’ study focused on first and premier division handball clubs in southern region. Its objectives were to develop a performance measurement scale for administrators of these clubs and to assess their job performance.  first and premier division handball clubs in southern region – researcher used descriptive method with survey and correlational study approach, as it is appropriate method to solve research problem and achieve its objectives.  researcher defined research population.  deliberate method involved first and premier league handball clubs in southern region for 2023-2024 sports season, totaling (196) administrators.  research samples represented entire research population, thus research sample size reached (100% of research population.  research samples were divided using simple random sampling into three sections:  pilot study sample (16 administrators), construction sample (100 administrators), and application sample (80 administrators).  most important conclusion is that job performance scale was built and is suitable for measuring job performance of sports club administrators in southern region in handball.